Antibacterial agents produced by lactic acid bacteria isolated from threadfin salmon and grass shrimp - Nordin, Noordiana; Abu Bakar, Fatimah; A. S., Mun (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Lactic acid bacteria (LAB) are non-pathogenic bacteria that have an important role in human daily life. LAB produce antimicrobial agents, such as bacteriocins, diacetyl and hydrogen peroxide which help to extend the shelf life of food products. In this study, LAB were isolated from selected seafood; threadfin salmon and grass shrimp. Antibacterial activity of LAB extracts against Salmonella typhimurium, Listeria monocytogenes, Bacillus cereus and Escherichia coli were determined using the disc diffusion method. Three strains of LAB were selected for the characterization of antibacterial agents produced by LAB. The parameters such as pH, heat, incubation period and medium, were analyzed in this experiment. Changes in environmental parameters affected the activity of antibacterial agents. The antibacterial agents produced by LAB were generally heat stable and stable in a wide range of pH levels. However, the inhibition activity of LAB was destroyed with a heat treatment of 121°C, and the antibacterial effect was reduced at a pH of 12, which occurs in most strains. The medium containing NaCl enhanced the antibacterial activity of P1S1 and P3S3 strains against S. typhimurium, L. monocytogenes and E. coli. Moreover, the antibacterial agents exhibited the greatest inhibition activity at incubation times between 24 and 72 h. The antibacterial activity was reduced after an incubation time of 96 h. The characterization of antibacterial agents aids in the improvement of food products safety.